Ethics in Marketing: isolated action or business? - Filho, Miguel Arantes Normanha (Review of Business Management, 2007)
This article, about the ethics in marketing, presupposes that it does not exist if it is not inserted in business ethics. It cannot be understood and defined like a subject of academy study away from the ethics of business. Speaking about marketing ethics requires solid marketing knowledge; in this way its definition, concepts, understanding and limitations are detailed for broader knowledge. The ethics in marketing is inserted in business since a marketing plan is related to the strategic plan of the company and ethics of business posture is defined intrinsically or extrinsically in the organizational mission. Key-words: Marketing. Ethics. Ethics in marketing. Ethics of business.